Understanding politics ideas, institutions & issues - Magstadt, Thomas M. (Thomson higher Education, 2006)
[This book], the proven, best-selling introductory text for Introduction to Political Science, examines the complexities of politics and government in a way that students will find immediately fascinating. Solidly based on three fundamental premises-that politics is a pervasive force in modern society, that government is too important to be left in the hands of the few, and that in a democracy everyone has both the opportunity and the obligation to participate in public life-the text builds on these beliefs, and seeks to "educate to participate." [This book] focuses on such pertinent concepts as democracy, dictatorship, citizenship, voting behavior, elections, leadership, ideologies, war, revolution, world politics, and public policy-fundamental concepts that provide students with a view of politics and economics that is at once lucid, nuanced, and empowering.